GENE ENGINEERING FOR PRODUCTION COLD-TOLERANT SWEET POTATO (IPOMOEA BATATAS) - Zhambakin K.Zh; Shamekova M.Kh; Zhapar K.K (Academic Journal of Physical and Chemical Sciences, 2019)
Sweet potato is produced in more than 100 countries as food security product and. More than 105 million tons are produced annually. Despite the fact that sweet potato are tropical plant, cultivation prospects in temperate zones is optimistic. The main limiting factor in the distribution of sweet potato in Kazakhstan is the cold factor. Traditional breeding methods have limitations for success production of cold tolerant agricultural plants. Genetic engineering is the most effective approach for increasing plant tolerance to biotic and abiotic factors, method allows gene transfer and directionally regulate the gene expression. The article discusses the use of various genes and transcription factors for producing cold tolerant sweet potato cultivars.